2019
DOI: 10.3390/w11010075
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Surface and Subsurface Water Storage in the Lower Mekong Basin (Vietnam and Cambodia) from Multisatellite Observations

Abstract: In this study, we estimate monthly variations of surface-water storage (SWS) and subsurface water storage (SSWS, including groundwater and soil moisture) within the Lower Mekong Basin located in Vietnam and Cambodia during the 2003–2009 period. The approach is based on the combination of multisatellite observations using surface-water extent from MODIS atmospherically corrected land-surface imagery, and water-level variations from 45 virtual stations (VS) derived from ENVISAT altimetry measurements. Surface-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…This study shows the great potential of SAR Sentinel-1 observations for monitoring spatial-temporal dynamics of small lakes, especially over tropical regions where the use of optical remote sensing is normally limited (Pham-Duc et al, 2019). However, several limitations of this study can be listed.…”
Section: Discussionmentioning
confidence: 87%
“…This study shows the great potential of SAR Sentinel-1 observations for monitoring spatial-temporal dynamics of small lakes, especially over tropical regions where the use of optical remote sensing is normally limited (Pham-Duc et al, 2019). However, several limitations of this study can be listed.…”
Section: Discussionmentioning
confidence: 87%
“…The spatial temporal variation of TWS and root zone soil moisture are estimated using GRACE and GLEAM dataset, respectively, and the variation of SWS is estimated using Eq. (2) 64,67 . Therefore, monthly variation of groundwater can be calculated as the difference between variations of TWS, and root zone soil moisture and SWS (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…This dryness effect on ecosystem productivity cannot be detected in the annual scale assessment (Brookshire and Weaver, 2015;Yao et al, 2020). These results imply that pre-growing season hydroclimate conditions play a key role in the follow-on vegetation growth and production (Kong et al, 2020;Piao et al, 2006;Wang et al, 2019), and that vegetation dynamics are subject not only to atmospheric changes but also water resource availability even in this humid subtropical radiationand rain-abundant region, while vegetation development is not dominant in reducing water availability. The causal role of vegetation in water decline has been reported mostly at a shorter timescale, like daily or sub-daily, such as the studies in a poplar stand in northwestern China (Shen et al, 2015), a pine-dominated catchment in Sierra Nevada, USA (Kirchner et al, 2020), and a mixed forest in the Czech Republic (Deutscher et al, 2016), which demonstrated that sap flow by trees led to decline in groundwater level and streamflow.…”
Section: Interactive Roles Of Water Supply Demand and Vegetation Changesmentioning
confidence: 96%
“…The differences in EVI and GPP response to hydroclimate variables may lie in the way these two parameters are calculated, especially given that GPP is formulated by atmospheric variables like temperature, vapor pressure deficit, and photosynthetically active radiation (Pei et al, 2020). Because of the asynchrony in the atmospheric variables and vegetation greenness (Kong et al, 2020;Piao et al, 2006), the GPP and EVI would also have some inconsistency in time. This would then further indicate that it should be given more caution when choosing a parameter (EVI, NDVI, SIF, or GPP) to better represent vegetation phenological features, which is still lacking in the literature for discussion (Kong et al, 2020;.…”
Section: Interactive Roles Of Water Supply Demand and Vegetation Changesmentioning
confidence: 99%